2023
DOI: 10.1002/cam4.5824
|View full text |Cite
|
Sign up to set email alerts
|

Androgen promotes squamous differentiation of atypical cells in cervical intraepithelial neoplasia via an ELF3‐dependent pathway

Abstract: Background Since the human papillomavirus vaccines do not eliminate preexisting infections, nonsurgical alternative approaches to cervical intraepithelial neoplasia (CIN) have been required. We previously reported that FOXP4 (forkhead box transcription factor P4) promoted proliferation and inhibited squamous differentiation of CIN1‐derived W12 cells. Since it was reported that FOXP expressions were regulated by the androgen/androgen receptor (AR) complex and AR was expressed on the CIN lesions, in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Recently, we reported that forkhead box transcription factor P4 (FOXP4) is associated with the androgen/AR pathway in cervical intraepithelial neoplasia cells 15 . FOXP4 was expressed in human cell lines of ECC, HEC50B, HEC108, and HEC265 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that forkhead box transcription factor P4 (FOXP4) is associated with the androgen/AR pathway in cervical intraepithelial neoplasia cells 15 . FOXP4 was expressed in human cell lines of ECC, HEC50B, HEC108, and HEC265 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The empty vector (pCAGIPuro) and a human AR overexpression vector were described in a previous paper 15 . The protein-coding sequences of human and mouse FOXP4 to subclone into the pCAGIPuro vector were amplified by PCR using primers (Supplementary Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that androgens promote squamous differentiation of atypical cells in cervical intraepithelial neoplasia through an ELF3-dependent pathway ( Figure 3 ). 10
Figure 3 Role of androgens/AR in cervical FOXP4-related proliferation and squamous differentiation DHT/AR inhibits the functional regulation of FOXP4 (a nuclear transcription factor) and NOTCH3 (a differentiation-related gene) in cervical epithelial cells, promoting cell squamous differentiation and suppressing proliferation, thus promoting the progression of CIN from grade 1 to grade 3.
…”
Section: Research Background Overviewmentioning
confidence: 99%
“…Recently, androgen has been reported to be a new factor regulating squamous differentiation involved in the early progression of cervical intraepithelial neoplasia (CIN), suggesting a novel nonsurgical hormone-induced differentiation therapy could be used against CIN1 and CIN2 [ 35 ].…”
Section: Hormone Therapeutic Strategiesmentioning
confidence: 99%